Scabies among children in Ethiopia - Desta Marmara; Hailemichael Mulugeta; Steven Thygerson; Adane Ermias (International Journal of Public Health Science (IJPHS), 2022)
Scabies disease is a common and unacceptable disease among young children in developing countries including Ethiopia. This study assessed the prevalence and factors associated with scabies among 5-14 year old children in Boricha District, Sidama Zone, Southern Ethiopia. Multi-stage sampling was employed and children were examined for scabies followed by parent interviews. Descriptive statistic and multivariable analyses were used. Among 590 selected school age children, the prevalence of scabies was 98 (16.6%) [95% CI: 13.6-19.7]. No formal education status of mothers [3.20 , 95% CI (1.03-9.90)], poor household wealth index [3.14, 95% CI (1.10-8.91)], children age 10-14 years [1.84, 95% CI (1.02-3.323)], practice of sharing a bed with a person who had itching lesion [3.38, 95% CI (1.51-7.58)], skin contact with person who had itching lesion [11.67, 95% CI (5.07-26.9)], family member with itchy signs [12.7, 95% CI (5.3-30.6)], frequency of bath of once in more than every two weeks [3.52, 95% CI (1.46-8.74)] were significantly associated with the scabies disease. The prevalence of scabies in the study area was substantially high. Family socioeconomic characteristics and hygiene practice were associated with scabies. Prevention should be focused on economic empowerment and hygiene-related interventions.